X Chromosome-Specific Repeats in Non-Domestic Bovidae - Kubickova, Svatava; Kopecna, Olga; Cernohorska, Halina; Rubes, Jiri; Vozdova, Miluse (Genes, 2024)
Repetitive sequences form a substantial and still enigmatic part of the mammalian genome. We isolated repetitive DNA blocks of the X chromosomes of three species of the family Bovidae: Kobus defassa (KDEXr sequence), Bos taurus (BTAXr sequence) and Antilope cervicapra (ACEXr sequence). The copy numbers of the isolated sequences were assessed using qPCR, and their chromosomal localisations were analysed using FISH in ten bovid tribes and in outgroup species. Besides their localisation on the X chromosome, their presence was also revealed on the Y chromosome and autosomes in several species. The KDEXr sequence abundant in most Bovidae species also occurs in distant taxa (Perissodactyla and Carnivora) and seems to be evolutionarily older than BTAXr and ACEXr. The ACEXr sequence, visible only in several Antilopini species using FISH, is probably the youngest, and arised in an ancestor common to Bovidae and Cervidae. All three repetitive sequences analysed in this study are interspersed among gene-rich regions on the X chromosomes, apparently preventing the crossing-over in their close vicinity. This study demonstrates that repetitive sequences on the X chromosomes have undergone a fast evolution, and their variation among related species can be beneficial for evolutionary studies.
Keywords: Cattle; chromozom Y; Chromosomes, Human, X; vysoká zvěř; skot; Y Chromosome; Repetitive Sequences, Nucleic Acid; Antelopes; repetitive sequence; qPCR; lidské chromozomy X; antilopy; FISH; Animals; lidé; Humans; zvířata; sequence analysis; DNA; X chromosome; repetitivní sekvence nukleových kyselin; laser microdissection; Deer; Bovidae